Three-Tier Prognostic Index in Young Adults With Advanced Gastric Cancer - Chen, Guang-Liang; Huang, Yan; Zhang, Wen; Pan, Xu; Feng, Wan-Jing; Zhao, Xiao-Ying; Zhu, Xiao-Dong; Li, Wen-Hua; Huang, Mingzhu; Chen, Zhi-Yu; Guo, Wei-Jian (Frontiers in Oncology, 2021)
Purpose To characterize clinical features and identify baseline prognostic factors for survival in young adults with advanced gastric cancer (YAAGC). Materials and Methods A total of 220 young inpatients (age less than or equal to 40 years) with an initial diagnosis of advanced gastric cancer were retrospectively enrolled in this study. Results Of a consecutive cohort of 220 patients with YAAGC, the median overall survival (OS) time was 16.3 months. One-year survival rate was 43.6% (95% CI: 36.5 to 50.7). In this cohort, a female (71.4%, n = 157) predominance and a number of patients with poorly differentiated tumors (95.9%, n = 211) were observed. In the univariate analysis, OS was significantly associated with neutrophil–lymphocyte ratio (NLR) (≥3.12), hypoproteinemia (<40 g/L), presence of peritoneal or bone metastases, and previous gastrectomy of primary tumor or radical gastrectomy. In multivariate Cox regression analysis, hypoproteinemia [hazard ratio (HR) 1.522, 95% CI 1.085 to 2.137, p = 0.015] and high NLR level (HR 1.446, 95% CI 1.022 to 2.047, p = 0.021) were two independent poor prognostic factors, while previous radical gastrectomy was associated with a favorable OS (HR 0.345, 95% CI 0.205 to 0.583, p = 0.000). A three-tier prognostic index was constructed dividing patients into good-, intermediate-, or poor-risk groups. Median OS for good-, intermediate-, and poor-risk groups was 36.43, 17.87, and 11.27 months, respectively. Conclusions Three prognostic factors were identified, and a three-tier prognostic index was devised. The reported prognostic index may aid clinical decision-making, patient risk stratification, and planning of future clinical studies on YAAGC.